Komputer sebagai Media Animasi Konten Pembelajaran PAI - Miftakhul Wahid Fauzan; Agus Purwowidodo; Zaini Fasya (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2023)
Islamic religious education has the potential to form intellectually, emotionally, and spiritually superior learners. The role of educators is very important in creating a conducive learning environment. Although students have different learning styles, learning is often constrained by the buildup of theory, the dominance of lecture methods, and the limited use of technology. One solution to overcome this is to strengthen the use of resources and technologies, such as learning animations in PAI. This article aims to examine the nature of animation in learning, the steps of animation production, and the implementation of computers in the production of PAI content animation. The literature study method is used by utilizing primary and secondary sources to answer the purpose of writing. The conclusions that can be drawn are: 1) Animation has a crucial role in learning media with a significant positive impact, especially on the effectiveness and efficiency of learning. Animation is also an alternative solution to overcome learning problems and facilitate the understanding of difficult concepts. 2) Animation production can be done easily and for free by following the steps available on the internet. Experts have unique methods in the pre-production, production, and post-production stages of animation that need to be considered in order to avoid gaps. 3) Computers have an important role in the production of interesting animations. The process of planning, implementation, and evaluation is a crucial stage. However, success depends not only on the computer, but also on the ability of the teacher. Knowledgeable and skilled teachers will be able to produce animations well.